2016
DOI: 10.22159/ajpcr.2016.v9s3.14753
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Relation Between Body Mass Index and Dysmenorrhea and Its Impact on Daily Activities of Medical Students

Abstract: Objective: Dysmenorrhea is a condition, in which there is a severe, painful, cramping sensation in the lower abdomen which occurs just before or during the menses. It has a major impact on the quality of life and social and occupational roles of females in the society. It also results in insignificant work, school, and college absences in girls. As previous studies have failed to show a definite relation between dysmenorrhea and body mass index (BMI), the aim of our study was to find out an association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
(11 reference statements)
6
15
2
4
Order By: Relevance
“…26,27 The present study revealed that UW females have a significantly higher prevalence of dysmenorrhea as compared to the OB ones. These findings are line with few previous studies.. 8,12,13,28,29 Chauhan et al narrates that all girls of their study group with moderate and severe dysmenorrhea had BMI < 16.5, but a drawback of this study was that 81% of their total study participants were only UW females, and none of the subject was OW or OB. This unequal distribution of subjects in different BMI groups may have caused a bias in the results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…26,27 The present study revealed that UW females have a significantly higher prevalence of dysmenorrhea as compared to the OB ones. These findings are line with few previous studies.. 8,12,13,28,29 Chauhan et al narrates that all girls of their study group with moderate and severe dysmenorrhea had BMI < 16.5, but a drawback of this study was that 81% of their total study participants were only UW females, and none of the subject was OW or OB. This unequal distribution of subjects in different BMI groups may have caused a bias in the results.…”
Section: Discussionsupporting
confidence: 90%
“…6 Some studies reveal that there is no relationship between BMI and dysmenorrhea, 6,[9][10][11] whereas increased prevalence of PD is documented in underweight (UW) subjects by other authors. 8,12,13 Still some other data is suggestive of a positive association between increased BMI and PD. 14 In addition, the study results of Hong et al provide a U shaped relationship between BMI and PD, indicating that both the UW and overweight (OW) + obese (OB) females are at a higher risk of having PD.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results contradict another study findings reported by Chauhan [11], who found the frequency of dysmenorrhea to be greatest in the underweight group. [11,12] On the same time this result goes online with other study findings where the percentage of students having mild and moderate pain has low BMI [13].…”
Section: Discussionsupporting
confidence: 83%
“…Studies have shown that various factors such as economic and social status, body mass index, age, education, and age of menarche affect menstruation (12,14). Adams et al found in their findings that women at lower ages are more likely to suffer from menstrual problems (15).…”
Section: Introductionmentioning
confidence: 99%